الأساليب الاتصالية لتجسيد البعد التمنوي بمناطق الظل _دراسة ميدانية على عدد من الجمعيات الناشطة بولاية سوق أهراس_ - بن شابي زين الدين; نشاد العربي (My University, 2022)
Summary: This study deals with the topic of "communication methods to embody the development dimension in the shadow areas", a field study on a number of active associations in the state of Souk Ahras, and it is a field study that addressed the problem of these associations use of communication methods in their development activities in the shadow areas from the perspective of the theoretical approach "participatory democracy" and Under the banner of systemic and formative paradigm from a communicative standpoint, this study aims to explore the mechanics of the work of civil society organizations and their ability to link between local administrations and citizens living in shadow areas, in order to clarify the development goals by clarifying the programs established in this framework, where I started from the following main question:  What are the communication methods used by the associations under study to embody local development through local administration programs? From which emerged analytically the following sub-questions:  What are the communication methods directed to the associations under study by the local administration?  What are the communication methods directed by the associations to citizens living in the shadow areas?  What are the obstacles to the communication process to clarify the objectives of the development program in the shadow areas through the associations under study? In order to achieve the objectives of the study, the qualitative approach was used by employing the open interview tool with the heads of a number of associations active in the development field. Among the most important results of the study are the following: The personal, direct and verbal communication is the most important communication method that has been employed to link the associations under study with the local administrations on the one hand and the residents of the shadow areas on the other hand. The emergence of a number of psychological, organizational and technical obstacles, as well as obstacles related to respecting the communicative context. ------------------------------------ الملخص: تتناول هذه الدراسة موضوع "الأساليب الإتصالية لتجسيد البعد التنموي في مناطق الظل" دراسة ميدانية على عدد من الجمعيات الناشطة بولاية سوق أهراس، و هي دراسة ميدانية تناولت إشكالية إستعمال هذه الجمعيات للأساليب الإتصالية في نشاطها التنموي بمناطق الظلن من منظور المقاربة النظرية" الديمقراطية التشاركية" و تحت لواء البراديغم النسقي و التكويني من منطلق إتصالي، و تهدف هذه الدراسة إلى إستكشاف ميكانيزمات عمل هيئات المجتمع المدني و مدى قدرتها على الربط بين الإدارات المحلية و المواطنين القاطنين في مناطق الظل، من أجل توضيح الأهداف التنموية عبر توضيح البرامج المسطرة في هذا الإطار، حيث أنطلقت من التساؤال الرئيسي التالي:  ماهي الأساليب الإتصالية المتبعة من طرف الجمعيات محل الدراسة لتجسيد التنمية المحلية من خلال برامج الإدارة المحلية ؟ والذي انبثقت منه تحليليا الأسئلة الفرعية التالية:  ما هي الأساليب الإتصالية الموجهة للجمعيات محل الدراسة من طرف الإدارة المحلية ؟  ما هي الأساليب الإتصالية الموجهة من طرف الجمعيات للمواطنين القاطنين بمناطق الظل ؟  ما هي عوائق العملية الإتصالية لتوضيح أهداف برنامج التنمية في مناطق الظل من خلال الجمعيات محل الدراسة ؟ و لبلوغ أهداف الدراسة تم استخدام المنهج الكيفي من خلال توظيف أداة المقابلة المفتوحة مع رؤساء عدد من الجمعيات الناشطة في المجال التنموي. و من أهم نتائج الدراسة ما يلي:  أن الإتصال الشخصي و المباشر و اللفظي هو أهم أسلوب إتصالي تم توظيفه لربط الجمعيات محل الدراسة مع الإدارات المحلية من جهة و قاطني مناطق الظل من جهة أخرى.  بروز عدد من العوائق النفسية و التنظيمية و التقنية و العوائق المتعلقة باحترام السياق الاتصالي.
Keywords: الأساليب الإتصالية، الإتصال التنموي، المجتمع المدني، الديمقراطية التشاركية، البعد التنموي، العوائق الإتصالية